The Effect of Market Orientation and Entrepreneurial Orientation on The Marketing Performance of Palm Sugar Msmes in South Minahasa Regency, North Sulawesi: The Role of Competitive Advantage as A Mediating Variable - Raintung, Michael Ch.; Loindong, Sjendry S.R.; Kawet, Raymond Ch. (Jurnal Agroekoteknologi Terapan (JAT), 2026)
This study aims to analyze the influence of market orientation and entrepreneurial orientation on marketing performance, as well as examine the role of competitive advantage as a mediating variable. This study uses a quantitative approach with a survey method of 62 palm sugar MSME owners in South Minahasa Regency. The research instrument is a questionnaire that has been validated by the Pearson correlation test and tested for reliability by Cronbach's Alpha test. Data analysis was carried out using the SPSS Version 28 program, including descriptive statistics, classical assumption tests, and multiple linear regression analysis to test hypotheses. The results of the study show that market orientation and entrepreneurial orientation have a positive and significant effect on competitive advantage and marketing performance. In addition, competitive advantage has also been shown to play a significant mediating variable in the relationship between market orientation, entrepreneurial orientation, and marketing performance. The conclusion of this study shows that palm sugar MSMEs that have a strong market orientation and entrepreneurship will be able to create a competitive advantage, which will ultimately improve their marketing performance. The results of this study are expected to provide input for MSME owners, the government, and other stakeholders in developing strategies to improve the performance of MSMEs in the palm sugar sector. Keywords: Market Orientation, Entrepreneurial Orientation, Competitive Advantage, Marketing Performance, Palm Sugar MSMEs Abstrak. Penelitian ini bertujuan untuk menganalisis pengaruh orientasi pasar dan orientasi kewirausahaan terhadap kinerja pemasaran, serta memeriksa peran keunggulan bersaing sebagai variabel mediasi. Penelitian ini menggunakan pendekatan kuantitatif dengan metode survei terhadap 62 pemilik UMKM gula aren di Kabupaten Minahasa Selatan. Instrumen penelitian berupa kuesioner yang telah divalidasi dengan uji korelasi Pearson dan diuji reliabilitas dengan uji Cronbach’s Alpha. Analisis data dilakukan dengan menggunakan program SPSS Versi 28, meliputi statistik deskriptif, uji asumsi klasik, dan analisis regresi linier berganda untuk menguji hipotesis. Hasil penelitian menunjukkan bahwa orientasi pasar dan orientasi kewirausahaan berpengaruh positif dan signifikan terhadap keunggulan bersaing serta kinerja pemasaran. Selain itu, keunggulan bersaing juga terbukti berperan sebagai variabel mediasi yang signifikan dalam hubungan antara orientasi pasar, orientasi kewirausahaan, dan kinerja pemasaran. Simpulan penelitian ini menunjukkan bahwa UMKM gula aren yang memiliki orientasi pasar dan kewirausahaan yang kuat akan mampu menciptakan keunggulan bersaing, yang pada akhirnya akan meningkatkan kinerja pemasaran mereka. Hasil penelitian ini diharapkan dapat memberikan masukan bagi pemilik UMKM, pemerintah, dan pemangku kepentingan lain dalam mengembangkan strategi untuk meningkatkan kinerja UMKM di sektor gula aren. Kata Kunci: Orientasi Pasar, Orientasi Kewirausahaan, Keunggulan Bersaing, Kinerja Pemasaran, UMKM Gula Aren